Efisiensi pemupukan fosfat, ketahanan terhadap kekeringan dan pertumbuhan kacang tanah (Arachis hypogaea L.) dengan inokulasi jamur mikoriza vesikular-arbuskular pada tanah berkapur=Phospate fertilizer application effici - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This study was carried out to investigate the effects of Vesicular-Arbuscular Mycorrhizae (VAM) inoculation on phosphate fertilizer application efficiency, drought stress resistance and the growth of peanut (Arachis hypogaea L.) grown on calcareous soils. Factorial Completely Randomized Design (CRD) with five replicates were used in this experiment. The first factor was two levels of VAM inoculation, i.e. Mo : without inoculation and M1 : inoculated with Glomus fasciculatum. The second factor consisted of four levels of phosphate fertilizer (SP-36) application, i.e. Po : without phosphate fertilizer, P1 : 0.08 g, P2 : 0.16 g, and P3 : 0.24 g/polybag, respectively. And the third factor was three levels of plant watering, frequency, i.e. Ao : watered everyday, Al : watered once in three days and A2 : watered once in five days, until field capacity. Plants were grown on 3 kg of sterile calcareous soils added by compost of ten gram/polybag and legin in the polybag and harvested at thirty days after planting.The measurement parameters including percentage of mycorrhiza infection, plant growth (dry weight of shoot and root, shoot/root ratio, relative growth rate, number and weight of effective nodule), total shoot P content and percentage increase of plant shoot P concentration. Collected data were analyzed by Analysis of Variance (Anova), followed by Duncan's Multiple Range Test (DMRT) at 5% level of significant. The result of this experiment showed that percentage of VAM infection was 76,97% on average. Mycorrhizal colonisation significantly increased plant growth (dry weight of shoot, shoot/root ratio, relative growth rate, number and weight of effective nodule), and total shoot P content. Symbiotic association with VAM also enhanced efficiency of phosphate fertilizer application and drought stress resistance of peanut on calcareous soils.